The interior of Scoresby Sund Church, Greenland. 1930 : Det indre af Scoresby Sund Kirke, Grønland. 1930 - Petersen, Sofie (University of Southern California Digital Library (USC.DL), 2015)
The interior of Scoresby Sund Church, Greenland. 1930